Exploratory trial of a school-based alcohol prevention intervention with a family component: Implications for implementation. Issue 4 (6th June 2016) - Segrott, Jeremy; Rothwell, Heather; Pignatelli, Ilaria; Playle, Rebecca; Hewitt, Gillian; Huang, Chao; Murphy, Simon; Hickman, Matthew; Reed, Hayley; Moore, Laurence
Abstract : Purpose: – Involvement of parents/carers may increase effectiveness of primary school-based alcohol-misuse prevention projects through strengthening family-based protective factors, but rates of parental engagement are typically low. This paper reports findings from an exploratory trial of a school-based prevention intervention – Kids, Adults Together (KAT), based on the Social Development Model, which aimed to promote pro-social family communication in order to prevent alcohol misuse, and incorporated strategies to engage parents/carers. The purpose of this paper is to assess the feasibility and value of conducting an effectiveness trial of KAT. Design/methodology/approach: – The study was a parallel-group cluster randomised exploratory trial with an embedded process evaluation. The study took place in south Wales, UK, and involved nine primary schools, 367 pupils in Years 5/6 (aged 9-11 years) and their parents/carers and teachers. Questionnaires were completed by pupils at baseline and four month follow-up, and by parents at six month follow-up. Findings: – Overall KAT was delivered with good fidelity, but two of five intervention schools withdrew from the study without completing implementation. In total, 50 per cent of eligible parents participated in the intervention, and KAT had good acceptability among pupils, parents and teachers. However, a number of "progression to effectiveness trial" criteria were not met. Intermediate outcomes on family communication (hypothesised to prevent alcohol misuse) showed insufficient evidence of an intervention effect. Difficulties were encountered in identifying age appropriate outcome measures for primary school-age children, particularly in relation to family communication processes. The study was unable to find comprehensive methodological guidance on exploratory trials. Research limitations/implications: – It would not be appropriate to conduct an effectiveness trial as key progression criteria relating to intervention and trial feasibility were not met. There is a need for new measures of family communication which are suitable for primary school-age children, and more guidance on the design and conduct of exploratory/feasibility trials. Originality/value: – KAT achieved high rates of parental involvement, and its theoretical framework and processes could be adapted by other interventions which experience difficulties with recruitment of parents/carers.